Temporary Intermediates of L-Trp Along the Reaction Pathway of Human Indoleamine 2, 3-Dioxygenase 1 and Identification of an Exo Site. (December 2021) - Mirgaux, Manon; Leherte, Laurence; Wouters, Johan
Protein dynamics governs most of the fundamental processes in the human body. Particularly, the dynamics of loops located near an active site can be involved in the positioning of the substrate and the reaction mechanism. The understanding of the functioning of dynamic loops is therefore a challenge, and often requires the use of a multi-disciplinary approach mixing, for example, crystallographic experiments and molecular dynamics simulations. In the present work, the dynamic behavior of the JK-loop of the human indoleamine 2, 3-dioxygenase 1 hemoprotein, a target for immunotherapy, is investigated. To overcome the lack of knowledge on this dynamism, the study reported here is based on 3 crystal structures presenting different conformations of the loop, completed with molecular dynamics trajectories and MM-GBSA analyses, in order to trace the reaction pathway of the enzyme. In addition, the crystal structures identify an exo site in the small unit of the enzyme, that is populated redundantly by the substrate or the product of the reaction. The role of this newer reported exo site still needs to be investigated.